Sr Isotopic Composition of NIES Certified Reference Material No. 28 Urban Aerosols - Yamakawa, Akane; Nagano, Kimiyo; Ukachi, Miyuki; Onishi, Kaoru; Yamashita, Katsuyuki; Shibata, Tomoki; Takamiya, Kazunari; Kani, Tomomi; Bérail, Sylvain; Donard, Olivier F. X.; Amouroux, David (Frontiers in Environmental Chemistry, 2021)
An interlaboratory study of the National Institute for Environmental Studies (NIES) certified reference material (CRM) No. 28 Urban Aerosols collected from the filters of a central ventilating system in a building in the Beijing city center from 1996 to 2005 was performed to obtain an information value of the Sr isotopic composition. The Sr isotopic composition was measured using multi-collector-inductively coupled plasma-mass spectrometry (MC-ICP-MS) to confirm the CRM’s within- and between-bottle homogeneity, and the results showed a 87Sr/86Sr ratio of 0.710227 ± 0.000019 (2SD, n = 18). The Sr isotopic compositions were intercompared using thermal ionization mass spectrometry (TIMS), which showed good agreement with values obtained at NIES. Subsequently, a consistent 87Sr/86Sr ratio was observed between two dissolution (hotplate vs. high-pressure bomb) and Sr separation (Sr spec resin vs. cation exchange resin) methods. To validate and reproduce the accuracy of our analytical methods, the Sr isotopic compositions of secondary reference materials, JB-1b and JA-2, were also measured. Our results showed that NIES CRM No. 28 is appropriate for the quality control of Sr isotope measurements of particulate matter analyses for environmental and geochemical studies.